Teores de B-Caroteno e A-tocoferol presentes na microalga Spirulina (Arthrospira) Platensis cultivada com diferentes fotoperíodos - Saboya, Jefferson Pablo de Sousa (2010)
The microalga cyanophyceae Spirulina platensis has been commercialized and studied due to its high nutritional value. It has shown to be a rich source of a great variety of vitamins, minerals, proteins, polyunsaturated fatty acids, carotenoids, phycobilins, and polysaccharides that exhibit potential therapeutic properties. The aim of the present work was to evaluate the content of -carotene and -tocopherol in S. platensis cultivated in laboratory under different conditions of photoperiods. S. platensis was cultivated within six 20-liter reservoirs under four different illumination conditions. The first culture was grown under 8- hour light (L) and 16-hour dark (D) photoperiod; the second, 12 L and 12 D photoperiod; the third, 16 L and 8 D photoperiod, and the forth cultivation condition was constant illumination. The reservoirs were placed side by side in two wood chambers, where room temperature was kept at 28 ± 2°C with a cooler (220 V). The water surface illumination of 78.1 μE cm-2 s-1 was supplied by two 40-Watt fluorescent lamps. The cultures were monitored by spectrometry at 680 nm and by counting microalga filaments (trichomes) under an optical microscope. The simultaneous analysis of carotenoids and tocopherols was performed by high performance liquid chromatography in a Waters Spherisorb-Hichrom S5 ODS-2 (4.6 x 250 mm) column using MeOH:THF (90:10, v/v) as mobile phase, delivered at 1.5 mL min-1. The detector was set at 450 nm and 292 nm for carotenes and tocopherols, respectively. For the extraction of both compounds, three portions of 0.1 g lyophilized Spirulina were suspended in 10 mL methanol:MiliQ water (90:10, v/v). The mixture was homogenized with a 7% potassium hydroxide aqueous solution, brought to a water bath at 70°C for 30 min, for saponification, followed of partitioning into n-hexane which was evaporated to dryness. The residues were suspended in 1 mL methanol, and 100 μL aliquots were manually injected in the chromatographic system. -Carotene was detected in the biomass obtained from all the cultures and a-tocopherol was detected only in 8 L and 16 D and 12 L and 12 D photoperiods cultures. -Tocopherol, on the other hand, was not detected. The content of -carotene varied with illumination intensity and in the cultivation performed under constant illumination both maximum productivity and highest -carotene content were reached rapidly